Time trends of neoadjuvant chemotherapy for early breast cancer - Riedel, Fabian; Hoffmann, Ann Sophie; Moderow, Mareike; Heublein, Sabine; Deutsch, Thomas M.; Golatta, Michael; Wallwiener, Markus; Schneeweiss, Andreas; Heil, Jörg; Hennigs, André (International journal of cancer, 2020)
Neoadjuvant chemotherapy (NACT) in early breast cancer (EBC) enables in vivo sensitivity testing and less radical surgery as compared to primary surgery and adjuvant chemotherapy (ACT). The aim of our study is to illustrate trends of systemic treatment of EBC. The study analyzed chemotherapy usage and time trends for patients with EBC treated at 104 German breast units between January 2008 and December 2017. The data were obtained through a quality-controlled benchmarking process. Altogether, 124 084 patients were included, of whom 46 279 (37.3%) received chemotherapy. For 44 765 of these cases, detailed information on systemic treatment and surgery were available. Overall use of chemotherapy declined from 42.0% in 2008 to 32.0% in 2017. During that same time, the proportion of NACT increased from 20.0% to 57.7%, irrespective of tumor subtype. The pathological complete response (pCR) rate (defined as ypT0 ypN0) at surgery after NACT increased from 15.0% to 34.2%. The results from this large cohort from the clinical routine reflect the refined indications for chemotherapy in EBC.
First published: 28 May 2020
Gesehen am 05.11.2021